Development of a Pair Check Cooperative-Based Zig-Zag Book to Improve the Writing Skills of Elementary School Students - Nur Sinta, Mawar; Sismulyasih SB, Nugraheti (Journal of Integrated Elementary Education, 2025)
This research and development (R&D) aimed at creating educational media designed to enhance skills in writing procedural texts. The research process followed eight key stages: identifying potential issues, data collection, product design, design validation, design revision, product trials, further product revisions, and concluding with usage trials. The participants in this study included fourth-grade students from Ngaliyan 05 Elementary School and Wonosari 02 Elementary School. The findings indicated a clear need among teachers and students for learning media to support their educational goals effectively. In response, the researchers developed the Zig-zag Book media based on the Pair Check Cooperative Learning method. This media encompasses a concise summary of the material, examples of procedural texts accompanied by visuals, student worksheets, and learning evaluations. Feedback from both students and teachers underscored several advantages of the developed media: it features an engaging design with bright colors that appeal to elementary school children, offers a variety of texts, images, examples, and practice questions, and presents precise instructions for use, making it user-friendly. The material is articulated succinctly, employing language and terminology that is accessible and easily understood. Field trials revealed that the media's feasibility was rated at 85% for the content and 93% for the overall quality. Furthermore, students' learning outcomes exhibited significant enhancement, with pre-test and post-test results yielding an impressive N-gain of 72.07%. This evidence suggests that the Zig-zag Book media, based on the Pair Check Cooperative Learning method, effectively improves students' writing skills.